2021
DOI: 10.7554/elife.70452
|View full text |Cite
|
Sign up to set email alerts
|

Variation in human herpesvirus 6B telomeric integration, excision, and transmission between tissues and individuals

Abstract: Human herpesviruses 6A and 6B (HHV-6A/6B) are ubiquitous pathogens that persist lifelong in latent form and can cause severe conditions upon reactivation. They are spread by community-acquired infection of free virus (acqHHV6A/6B) and by germline transmission of inherited chromosomally-integrated HHV-6A/6B (iciHHV-6A/6B) in telomeres. We exploited a hypervariable region of the HHV-6B genome to investigate the relationship between acquired and inherited virus and revealed predominantly maternal transmission of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Some herpesviruses can integrate within the telomeres at the end of chromosomes in animals ( Gennart et al. 2015 , Wood et al. 2021 ), and more recently, some herpesvirus-related viruses were shown to integrate in the telomeres of thraustochytrid protists ( Collier et al.…”
Section: Resultsmentioning
confidence: 99%
“…Some herpesviruses can integrate within the telomeres at the end of chromosomes in animals ( Gennart et al. 2015 , Wood et al. 2021 ), and more recently, some herpesvirus-related viruses were shown to integrate in the telomeres of thraustochytrid protists ( Collier et al.…”
Section: Resultsmentioning
confidence: 99%
“…When we matched the candidate integration sites to public sequences using NCBI’s BLAST, all sequences matched to isolate HHV or endogenous HHV sequences. In particular, sequences matched to studies studying integrated HHV diversity [3, 56, 57, 21, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Connections between chromosomal ends and mobile elements have been described in diverse systems. Some herpesviruses can integrate within the telomeres at the end of chromosomes in animals (Gennart et al 2015;Wood et al 2021), and more recently, some herpesvirus-related viruses were shown to integrate in the telomeres of thraustochytrid protists (Collier et al 2023). In circular chromosomes of bacteria, many mobile elements integrate into the chromosome dimer resolution site located near the replication terminus (Midonet and Barre 2014;Midonet and Barre 2016).…”
Section: Ev-associated Plvs Encode Replication Genes Related To Mobil...mentioning
confidence: 99%